Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Hasil Belajar Siswa dalam Pembelajaran PAI Kelas V di SD 4 Banda Aceh - Uswatul Zahra; Saifullah Isri; Sri Mawaddah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The dynamics of the teaching and learning process in Islamic Education (PAI) demand more interactive methods to prevent student boredom. Therefore, this study aims to determine the effect of implementing the Problem-Based Learning (PBL) model in PAI learning at SD 4 Banda Aceh. This research utilized a quantitative approach with a pretest-posttest control group design, involving fifth-grade students as subjects. Data collection was conducted through pretests and posttests. Data analysis included the Shapiro-Wilk normality test, homogeneity test, and hypothesis testing via the Independent Sample t-Test, assisted by the SPSS version 23 application. The results indicated an improvement in student learning outcomes within the experimental class, which utilized the Problem-Based Learning model, compared to the control class that employed conventional learning methods. This is evidenced by the experimental class's average N-Gain score of 52.08%, which falls into the moderately effective category, whereas the control class only achieved 19.02%, falling into the ineffective category. Furthermore, the hypothesis testing using the Independent Sample t-Test on the N-Gain values showed a significance value (Sig. 2-tailed) of 0.000 < 0.05. Consequently, H0 is rejected, and Ha is accepted, meaning that the application of the Problem-Based Learning (PBL) model significantly affects student learning outcomes on the topic of almsgiving (sedekah) in the fifth grade of SD 4 Banda Aceh. This model can be used as an alternative to enhance the quality of innovative and relevant learning in Islamic Education. Keywords: Problem-Based Learning, Islamic Education, Student Learning Outcomes